Measurement and modelling of tropospheric reactive halogen species over the tropical Atlantic Ocean - A. S. Mahajan; J. M. C. Plane; H. Oetjen; L. Mendes; R. W. Saunders; A. Saiz-Lopez; C. E. Jones; L. J. Carpenter; G. B. McFiggans (Atmospheric Chemistry and Physics, 2010)
Although tropospheric reactive halogen chemistry is well studied in coastal and polar environments, the presence of halogens over the open ocean environment has not been widely reported. The impacts of halogens on the tropical open ocean marine boundary layer (MBL), in particular, are not well characterised. This paper describes observations of iodine monoxide (IO) and bromine oxide (BrO) over eight months in the tropical open ocean MBL, on the north-eastern side of São Vicente (Cape Verde Islands, 16.85° N, 24.87° W). The highest BrO mixing ratio observed was 5.6±1 pmol mol−1, while the maximum observed IO mixing ratio was 3.1±0.4 pmol mol−1. The average values seen between 09:00–17:00 GMT were ~2.8 pmol mol−1 for BrO and ~1.5 pmol mol−1 for IO; these averages showed little variability over the entire campaign from November 2006 to June 2007. A 1-dimensional chemistry and transport model is used to study the evolution of iodine species and quantify the combined impact of iodine and bromine chemistry on the oxidising capacity of the MBL. It appears that the measured fluxes of iodocarbons are insufficient to account for the observed levels of IO, and that an additional I atom source is required, possibly caused by the deposition of O3 onto the ocean surface in the presence of solar radiation. Modelling results also show that the O3 depletion observed at Cape Verde cannot be explained in the absence of halogen chemistry, which contributes ~45% of the observed O3 depletion at the height of measurements (10 m) during summer. The model also predicts that halogens decrease the hydroperoxy radical (HO2) concentration by ~14% and increase the hydroxyl radical (OH) concentration by ~13% near the ocean surface. The oxidation of dimethyl sulphide (DMS) by BrO takes place at a comparable rate to oxidation by OH in this environment. Finally, the potential of iodine chemistry to form new particles is explored and conditions under which particle formation could be important in the remote MBL are discussed.